2001
DOI: 10.1037/1064-1297.9.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole suppresses food restriction–induced increases in heroin self-administration in rats: Sex differences.

Abstract: The effects of ketoconazole, an inhibitor of corticosterone synthesis, were examined during food satiation and food restriction in male and female rats to determine whether increases in heroin self-administration prompted by food restriction were due to a stress response. Females self-administered more heroin infusions than males under both feeding conditions. Food restriction increased heroin infusions by an average of 96% for both females and males. Ketoconazole suppressed the increase due to food restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 73 publications
8
46
3
Order By: Relevance
“…Although a growing body of evidence suggests that females are more prone to drug self-administration than males (Alexander et al, 1978;Lynch and Carroll, 1999;Carroll et al, 2001;Cicero et al, 2003;Hu et al, 2004;Roth et al, 2004), we found no differences in the acquisition of male and female mice. However, it is noteworthy that choice accuracy for the morphine-reinforced arm of the maze reached a maximum in female WT mice, with over 95% of drug-reinforced responses for 4 out of 6 self-administration sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…Although a growing body of evidence suggests that females are more prone to drug self-administration than males (Alexander et al, 1978;Lynch and Carroll, 1999;Carroll et al, 2001;Cicero et al, 2003;Hu et al, 2004;Roth et al, 2004), we found no differences in the acquisition of male and female mice. However, it is noteworthy that choice accuracy for the morphine-reinforced arm of the maze reached a maximum in female WT mice, with over 95% of drug-reinforced responses for 4 out of 6 self-administration sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…This apparent "treatment" effect of reducing drug intake and impulsivity for the drug was greater in females than males (Fig. 4c, d, Table 4) and was consistent with the sex differences (females > males) found in several other studies using behavioral approaches, such as adding nondrug rewards like SACC in monkeys (Cosgrove and Carroll 2003), access to a running wheel in rats (Cosgrove et al 2002), or pharmacological treatments (Campbell et al 2002;Carroll et al 2001b;Cosgrove and Carroll 2004). These results suggest that females are more sensitive to rewarding effects of drugs and to treatments than males, and they may be more reward sensitive and/or less responsive to aversive events than males.…”
Section: Discussionsupporting
confidence: 83%
“…Women begin cocaine use at a younger age than do men (Griffin et al, 1989) and can become addicted to abused substances, such as cocaine, opiates, and alcohol, faster than do men (Lex, 1991). Similarly, female rodents demonstrate quicker acquisition of cocaine, methamphetamine, and nicotine intravenous self-administration than do males (Caggiula et al, 2002;Carroll et al, 2001;Roth and Carroll, 2004). Thus, these data suggest that females may be more vulnerable to effects of drugs of abuse.…”
Section: Introductionmentioning
confidence: 63%